Elektrichka - Yusupova, Mayram (Russia : VIB-Film, 2003)
Everyday situations and conversations between passengers on suburban trains around Moscow, recorded over a period of more than six months, provide an insight into contemporary Russian society, where modernity merges with traditional practices to form an open-ended story. All generations, lifestyles, and occupations are represented on suburban trains, a microcosm so close to - and yet so different from - life in the capital. The suburban train is at once an improvised market, a place to share a life story, to discuss politics, and to make friends. The camera, attentive and discreet, becomes a thoughtful passenger on this journey.
Verzio Film Festival Submission
Duration: 00:30:00
Keywords: Russia